Second Regional seminar on fisheries management and development cooperation in the lower Mekong Basin: (Mekong river commission Secrettariat, 1995)
The aims of the seminar is stated in the opening address by the officer-in-charge of the MRC Secretariat and director of the resources. The organizers are convinced that the advice given by the participant in the seminar may lead to a solid cooperation on fisheries management and development the region.